ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, DAN CAPITAL PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK - Ningsih, Lusia Novita; Reviandani, Wasti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to analyze the soundness level of a bank using the risk profile method, good corporate governance, earnings and capital at PT Bank Tabungan Negara (Persero) Tbk. This research uses a quantitative descriptive approach. The type of data used in this study is secondary data, namely in the form of financial reports from PT Bank Tabungan Negara (Persero) Tbk. for five years from 2017 to 2021, 30 company data were obtained. The analysis technique used in this study is to use the risk profile method, good corporate governance, profitability, and capital (RGEC). The results of the analysis show that PT Bank Tabungan Negara (Persero) Tbk. during the 2017-2021 period, it received a fairly healthy predicate (Composite Rating 3).